Synthesis and application of optical silver nanoparticles capped carbon dots as dual-mode sensors for trivalent chromium ions in dietary supplements - Ratchadaporn Seedad; Pornpimol Prayongpan; Wutthikrai Busayaporn; Kriangsak Songsrirote (Sensors International)
A facile method for trivalent chromium (Cr3+) ion determination using optical silver nanoparticles capped carbon dots (Ag@CDs) was developed. The optical responses via absorption and fluorescence of Ag@CDs in the presence of Cr3+ ion were detected. The nanocomposite showed maximum absorption wavelength at 406.0 nm, while emission wavelength appeared at 526.0 nm when excited at 406.0 nm. Optimal conditions for the Ag@CDs activity on Cr3+ ion detection were at pH 6, volume ratio between Ag@CDs and Cr3+ ion of 1.0:4.0, and reaction time of 20 min. The linearity range of the detection was 0.1–10.0 mg/L. In the absorption mode, the limit of detection (LOD) and limit of quantification (LOQ) were 0.10 mg/L and 0.31 mg/L, respectively. The fluorescence mode of detection showed LOD and LOQ of 0.06 mg/L and 0.18 mg/L, respectively. The dual-mode sensor was applied for Cr3+ ion quantification in dietary supplement samples because it is an essential micronutrient and widely used as supplement products. The recovery study of the spiked sample extracts was in the range of 96.86–103.05 %. The results showed good agreement with those from a conventional method of atomic emission spectrometry. The optical changing mechanism of the nanocomposite could be explained by the electron transfer from Ag@CDs to Cr3+.